New lower Givetian age miospores of the Phyllite-Quartzite Group, São Francisco da Serra Anticline, Iberian Pyrite Belt - Portugal - Pereira, Zélia (2009)
Palynostratigraphical analysis of Phyllite Quartzite (PQ) Group shales recovered froma drill core and outcrops at the São Francisco da Serra anticline, in the westernmost area of the Iberian Pyrite Belt, yielded a moderately preserved miospore assemblage assigned to the upper part of AD miospore Biozone, subzone Lem, of lower Givetian age. This is the oldest age recognized, up to this date, for any rocks in the Iberian Pyrite Belt.